PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBANTUAN KOMPUTER DENGAN LECTORA AUTHORING TOOLS PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP/MTS - Kintoko Kintoko; Imam Sujadi; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research is aimed to: 1) describe the Lectora Authoring Tools (LAT)-based learning media application product design for computer-based Mathematics learning with the topic on geometry; 2) find out which media helped for better learning achievements: a Lectora Authoring Tools (LAT)-based learning or without employing any media.This research is a Research and Development model (R & D). The development was done by referring to the 4-D model found by Thiagarajan which were then modified into 3-D consisting of ‘defining’, ‘designing’, and ‘developing’. The product evaluation was done by the learning material expert covering the following aspects, namely the learning material completeness, learning material quality, linguistic quality, and visual quality, then, the learning media expert evaluated the following aspects, namely the readability, the image quality, the compatibility, the audio quality, the layout, and the animation. There were four teachers and four peers evaluated the content and display aspects. The subjects of the tryout were Grade VIII students in SMP PGRI Kasihan Bantul: 15 students for the limited tryout and 30 others for the field tryout. The data were collected through questionnaires, observation sheets, and learning achievement tests The equilibrium test was conducted using t-test, with α = 0.05, thereby it could be concluded that the experimental and control groups were in equilibrium. The prerequisite test included normality one using Liliefors test and homogeneity test using Bartlett method. With α = 0.05, it could be concluded that the sample derived from the homogeneous and normally distributed population..The research findings show that: 1) the media produced were in the form of Compact Disk (CD) as well as the Exe extension media which can be run in all computer operating system. This media was developed by employing Thiagarajan’s development model which consisted of ‘defining’, ‘designing’, and ‘developing’, whereas, the computer-assisted Mathematics learning media by employing the Lectora Authoring Tools (LAT) development resulted in better learning quality based on the validity, practicality, and effectiveness aspects. Those aspects showed a very good learning outcome as the developed learning media were able to display a learning material with easily understood animation graphics; 2) learning by employing the Lectora media presented higher achievements than those without it. It was proven by the mean value of the LAT This is evidenced by the results of hypothesis testing indicated on achievement tests of two classes, the value of test t = 2.236 with a t-table value = 1.960, while for DK = {t | t <-1960 or t> 1.960} tcount DK Thus, the means H0 is rejected so it can be concluded achievement test results in the experimental class with the control group there was a difference class-based learning as much as 77.78, which was better than that without the LAT with the mean value of 72.38.Keywords: developments, learning media, geometry, Lectora Authoring Tools software, concept mastery, achievements